Endothelial-derived plasma exosome proteins in Alzheimer’s disease angiopathy - Abner, Erin L. (FASEB J, 2020)
Small cerebral vascular disease (SCeVD) demonstrated by white matter hyperintensity (WMH) on MRI contributes to the development of dementia in Alzheimer's disease (AD), but it has not been possible to correlate onset, severity, or protein components of SCeVD with characteristics of WMH in living patients. Plasma endothelial-derived exosomes (EDEs) were enriched by two-step immunoabsorption from four groups of participants with no clinical evidence of cerebrovascular disease: cognitively normal (CN) without WMH (CN without SCeVD, n = 20), CN with SCeVD (n = 22), preclinical AD (pAD) + mild cognitive impairment (MCI) without SCeVD (pAD/MCI without SCeVD, n = 22), and pAD/MCI with SCeVD (n = 16) for ELISA quantification of cargo proteins. Exosome marker CD81-normalized EDE levels of the cerebrovascular-selective biomarkers large neutral amino acid transporter 1 (LAT-1), glucose transporter type 1 (Glut-1), and permeability-glycoprotein (p-GP, ABCB1) were similarly significantly higher in the CN with SCeVD and pAD/MCI with SCeVD groups than their corresponding control groups without SCeVD. CD81-normalized EDE levels of Aβ40 and Aβ42 were significantly higher in the pAD/MCI with SCeVD group but not in the CN with SCeVD group relative to controls without SCeVD. Levels of normal cellular prion protein (PrPc), a receptor for amyloid peptides, and phospho-181T-tau were higher in both CN and pAD/MCI with SCeVD groups than in the corresponding controls. High EDE levels of Aβ40, Aβ42, and phospho-181T-tau in patients with WMH suggesting SCeVD appear at the pre-clinical or MCI stage of AD and therapeutic lowering of neurotoxic peptide levels may delay progression of AD angiopathy.